Preliminary Survey of Forest Nursery Diseases in Ethiopia - Regasa, Kumela; Beze, Weldesenbet (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2026)
The availability of a healthy stock of seedlings is fundamental for raising plantations. A survey was conducted from 2023 to 2024 to observe the occurrence of diseases in forest nursery seedlings in different zones of the Oromia and Amhara regions. During the survey, various plant species were examined for disease occurrence. It was found that E. camaldulensis, E. globulus, Acacia decurrens, Cupressus lusitanica, Grevillea robusta, A.indica, Juniperus procera, Pinus patula, and Dovyalis abyssinica were infected by a disease. The assessment recorded seven seedling diseases, with 12 fungal genera of pathogens isolated. The recorded symptoms of disease during the study included powdery mildew, damping-off, leaf spot, leaf blotch, rust, shoot dieback, and wilting. The pathogens identified from the recorded diseases symptoms were B.cinerea, Alternaria ,Pestalotiopsis spp., Podosphaera spp., Fusarium spp., R.solani, Cylindrocladium spp.,Uromycladium spp.,Phoma spp.and Pythium spp. Rhizoctonia solani was frequently isolated from the damping-off symptoms. Field observations indicated that damping-off on C.lusitanica and p.patula, as well as powdery mildew on Eucalyptus species, are becoming serious problems that limit the production of nursery seedlings. The infection of disease is greatly influenced by improper nursery practices during seedling production, location and type. Some the recorded diseases can cause losses in seedling quality and quantity which can affect plantation programs. The surveys reported here provide a foundation for understanding the status of forest nursery diseases in Ethiopia and serve as a useful reference for assessing current and future forest disease developments and management. Further study on inoculum sources and the morphological characteristics of pathogens associated with seedling diseases using molecular tools is also needed.